2013
DOI: 10.1089/end.2013.0061
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Percutaneous Nephrolithotomy for Simple and Complex Renal Caliceal Stones: A Comparative Analysis of More Than 10,000 Cases

Abstract: AbstractsPurpose: To determine whether minimally invasive PCNL (MPCNL) is as safe and effective in the management of complex renal caliceal stones as it is for simple renal stones. Patients and Methods: We retrospectively reviewed 5761(41.2%) simple caliceal stones (isolated renal pelvis including isolated calix) and 8223 (58.8%) complex caliceal stones (renal pelvis accompanying two calices at least) that were managed by MPCNL between 1992 nd 2011. The safety, efficacy, and outcome were compared and analyzed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 20 publications
2
56
1
3
Order By: Relevance
“…We had previously reported that MPCNL is a safe and effective therapeutic modality for this condition [1]. Nevertheless, using MPCNL in the management of staghorn stones is technically complicated, time consuming, and taxing to both the patients and the surgeons.…”
Section: Introductionmentioning
confidence: 99%
“…We had previously reported that MPCNL is a safe and effective therapeutic modality for this condition [1]. Nevertheless, using MPCNL in the management of staghorn stones is technically complicated, time consuming, and taxing to both the patients and the surgeons.…”
Section: Introductionmentioning
confidence: 99%
“…Reports of MPNL use in adults with a specially designed mini-nephroscope were published in 2001 [4]. Later on results in the adult population evolved with comparable success rates [5].…”
Section: Introductionmentioning
confidence: 99%
“…The success and complication rates in PCNL can vary according to the complexity of stone disease [12,13]. Calculi were commonly classified into simple or complex, pelvic or calyceal based on location, or single or multiple.…”
Section: Discussionmentioning
confidence: 99%